(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article explores the theme of “Leaving Eden” within various religious and literary contexts, emphasizing its representation of the shift from innocence to experience in humanity. By analyzing both Genesis and Paradise Lost, along with interpretations from different cultures and contemporary perspectives, it underscores the significance of this motif in examining free will, morality and redemption.